Experimental Study on Landslides of Loose Sediment Slope Induced by Stream Bed Incision - Huang, Kehan; Xu, Mengzhen; Wang, Zhaoyin (Frontiers in Earth Science, 2021)
Uplift of the Qinghai-Tibetan Plateau has resulted in rapid incision of rivers along the margin of the plateau. Landslides occur frequently as a consequence of increasing bank slope and potential landslide energy due to stream bed incision or lateral bank erosion on the concave banks at bends. The Fencha Gully is on the eastern margin of the Qinghai-Tibetan Plateau and is developing on a huge landslide body. Flume experiments were conducted on the base of the field investigation to study the mechanism of landslides induced by stream bed incision. The experiments were designed with a length scale ratio of 1:20. Landslides and stream bed incision with loose sediment were observed and analyzed. The results show that landslides are induced as a result of stream bed incision. The potential landslide energy is defined, which increases quickly with an effective incision depth coupling vertical incision and lateral bank erosion. The occurrence of landslides can be attributed to increasing incision depth and potential landslide energy. Results indicate that the critical effective incision depth is 4.0–6.0 m. A critical value of the potential landslide energy is found from the experiments. Landslides occur if the potential energy exceeds the critical energy, which is 2.24×104 t·m/s2 for the Fencha Gully. The incision depth and potential energy of landslides from the Fencha Gully agree well with the results.